Population features of the pea crab Dissodactylus crinitichelis Moreira, 1901 (Decapoda, Brachyura, Pinoteridade) associated with the sand-dollar Encope emarginata (Echinodermata, Echinoidea) in the southeastern Brazilian coast - de Paula, Julia Rodrigues; de Moraes, Isabela Ribeiro Rocha [UNESP]; Cobo, Valter José (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2023)
Crabs of the Dissodactylus genus are commonly found in symbiosis with other marine invertebrate organisms. This study describes the structure of the population of the Pinnotheridae crab Dissodactylus crinitichelis living in symbiosis with the sand dollar Encope emarginata on a temporal scale and over the size class distribution, sex-ratio, recruitment defined as the specimens of the two first size classes, and breeding period. Specimens were collected in sand bottoms at the infralittoral zone at Flamengo Beach in Ubatuba, in the northeastern coast of São Paulo state, using free diving performed by one diver from August 2017 to July 2018, for 30 minutes per month. 337 juvenile, 51 adult females, and 38 adult males were analyzed, comprising 12 ovigerous females. There was registered recruitment, in almost all months. The sex ratio was 1:1.3, with more females than males in the population. In March, there was a significant recruitment period with 337 juveniles in one sample. The maximum carapace width was 6.6mm in males and 7.65mm in females. The representative number of specimens in the first size class may provide information that D. crinitichelis presents some levels of spatial segregation in the population in this area and should be monitored for preservation.
Parâmetros populacionais do caranguejo-pêra Dissodactylus crinitichelis Moreira, 1901 (Decapoda, Brachyura, Pinoteridade) associado com a bolacha-do-mar Encope emarginata (Echinodermada, Echinoidea) no litoral sudeste brasileiro
Keywords: crustacea; ecology; Flamengo beach; symbiosis; Ubatuba